HUBUNGAN ANTARA TINGKAT PEMAHAMAN TEKNOLOGI INFORMASI (APLIKASI) DENGAN KINERJA KADER POSYANDU Studi Observasi Analitik Kader Posyandu di Wilayah Puskesmas Bangetayu Semarang - Elza Aisyah Rahma; Purwito Soegeng Prasetijono (Jurnal Riset Multidisiplin Edukasi, 2026)
The utilization of information technology in Posyandu activities is one of the efforts to enhance the effectiveness of community-based health services. Differences in the level of knowledge of information technology among cadres are presumed to influence their performance in recording, reporting, and delivering health services. This study aimed to determine the relationship between the level of knowledge of information technology (application) and the performance of Posyandu cadres in the working area of Bangetayu Community Health Center, Semarang City. This study employed a quantitative observational analytic design with a cross-sectional approach. A total of 76 cadres were selected using consecutive sampling. Data were collected through questionnaires and analyzed using univariate and bivariate methods with the Spearman correlation test. The results showed that most cadres had a low level of knowledge of information technology (42.1%). Cadre performance was relatively evenly distributed, with both good and moderate categories accounting for 34.2% each. The Spearman test indicated a significant relationship between the level of knowledge of information technology (application) and cadre performance (r = 0.370; p = 0.001). In conclusion, there is a statistically significant positive relationship with moderate strength between the level of knowledge of information technology (application) and the performance of Posyandu cadres.